Genetic Diversity Analysis of Onion (Allium cepa L.) from the Arid Region of Tunisia Using Phenotypic Traits and SSR Markers - Amel Chalbi; Hela Chikh-Rouhou; Najla Mezghani; Amine Slim; Oreto Fayos; Mohamed Sadok Bel-Kadhi; Ana Garcés-Claver (Horticulturae, 2023)
The present study was carried out to evaluate and characterize, for the first time, the genetic potential of a collection of onion (Allium cepa L.) local accessions from the arid region of southern Tunisia. The genetic diversity among 135 onion individuals, belonging to 23 accessions, was evaluated using microsatellite (SSR) markers and phenotypic information. A total of 35 alleles were generated with 11 SSRs. The polymorphic information content (PIC) value ranged from 0.08 to 0.95, with an average PIC of 0.43. The expected heterozygosity averaged 0.37, and the observed heterozygosity averaged 0.42. The analysis of molecular variance (AMOVA) revealed that 79% of genetic variation existed within individuals. Structure and cluster analysis grouped the accessions into two major clusters: landraces and pre-breeding lines. For the phenotypic traits evaluated, field trials were conducted in two different environments. Significant differences among accessions were shown, and for most traits, there was also a significant environmental effect and a significant interaction between environment and accession. Great variability was found for all the traits that could be exploited to create new varieties of onion adapted to local conditions by selecting appropriate parents in hybridization breeding.